(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to know the personality style and its relationship to self-realization among the students of the Faculty of Physical Education in the subject of gymnasticsThe research problem was identified in the following question:What is the nature of the relationship between the two variables of personality style (extraversion / introversion) and self-realization among the students of the Faculty of Physical Education in the gymnastics lesson?The research included five hypotheses, and was applied to students of the College of Physical Education - University of Baghdad. The two researchers relied to study this problem on the personality style scale and the self-realization scale, which were built because they were not available in the field of physical education. The researcher used the descriptive approach in the manner of correlational studies.